Local History Practice in the System of Bachelors-Historians Training: Experience and Prospects - Вовк, О.І.; Куделко, С.М. (Sciedu Press, 2022)
The article describes and summarizes the experience of conducting local history educational and productive practice for students of the first (bachelor's) level of education, majoring in “History and Archeology” at th e School of History, V.N.Karazin Kharkiv National University (Ukraine). The authors show that the set of principles and research methods, being the basis of this investigation, ensures reliability of the analysis and representativeness of the results. A re view of the latest publications on the topic confirmes its relevance and lack of development in the specialized literature. The article substantiates the important role and significance of the local history educational and productive practice for further p rofessional activity of the future graduates. The authors explain the main approaches to the organization of this form of educational activity in traditional conditions (among such approaches the implementation of creative projects in small groups, excur sions and expeditions). The article reveals the changes that took place in the process of organizing and conducting local history educational and productive practice after the outbreak of the coronary crisis. The approaches and methods, developed for the d istance passing of local history educational and productive practice, may be useful after returning to the traditional system of education. The authors, using a correlation regression analysis of the ratio of the number of students who underwent local hist ory educational and productive practice and the number of students speakers at the International Local History Conference of Young Scientists, found a moderate correlation between these indicators. The article concludes that the local history educational and productive practice encourages students to further research activity in the field of local history.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; university education, local history, practical training of students, educational and product; university education, local history, practical training of students, educational and product; university education, local history, practical training of students, educational and product; university education, local history, practical training of students, educational and product ive practice; distance learning